Kajian Yuridis Eksistensi dan Materi Ketetapan Majelis Permusyawaratan Rakyat Republik Indonesia dalam Hirarki Perundang-Undangan di Indonesia - Author: Saifudin; Dessy Ariani (Fakultas Hukum Universitas Islam Indonesia, 2015)
This study examines, first, what is the position of the People’s Consultative Assembly Decree in the hierarchy of laws in Indonesia? Second, which agency is authorized to examine the decree of People’s Consultative? This research is a normative law with statute approach. The results of this study concludes that, first, even though the People’s Consultative Assembly no longer authorized to issue decree laws of the People’s Consultative Assembly, but there are still three provisions of the Assembly are declared valid. So that the provisions of the People’s Consultative Assembly still has a position in the hierarchy of legislation. Second, the body which has the right to test the decree of People’s Consultative Assembly is still not yet exist, although in practice the application is submitted to the Constitutional Court and was turned down by the Constitutional Court on the grounds that the Constitutional Court does not have the authority to test the People’s Consultative Assembly.